Proving The Reading Ability of Children Aged 5-6 Years Through The Application of Picture Card Media - Ivana Rahmawati (International Journal of Social Service and Research, 2021)
This study was conducted to determine efforts to improve the reading ability of children aged 5-6 years through the application of image media in group B in TK PGRI Melati 2. To obtain data in this study the author used quantitative research methods, from the data generated through observation, the format of ability assessment. This research was conducted in group B PGRI Melati 2 Kindergarten with a total of 15 students. The purpose of this study is to improve reading skills by using interesting media images so that children are able to read and recognize the letters of the words in each picture. Not only using pictures that were done in this study, but children can make their own sentences using the picture cards. There is an aspect of language that is taken in this case, so that children get a lot of vocabulary for each of their vocabulary. Teachers can make interesting games too with this picture media. Using image media is also able to improve children's cognitive in recognizing every object or word in the picture, so that children understand and understand the real form of the image. The success of research using picture cards is very helpful in improving each word